Distribution of Giant Prawns (Macrobrachium rosenbergii) in the Mangrove Ecosystem Rawa Mekar Jaya Village Sungai Apit District Siak Regency Riau Province. - Riska Diani; Nur El Fajri; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract The mangrove ecosystem of the village of Rawa Mekar Jaya has been degraded due to illegal logging. The condition of water quality is influenced by various activities that take settlements, sago processing coastal activities of tides that cause changes in water salinity. This research was conducted in July 2019 in the mangrove/estuary ecosystem of the Rawa Mekar Jaya river. The purpose of this study was to determine the distribution patterns of giant prawns in the mangrove ecosystem of Rawa Mekar Jaya Village. There are 3 research stations (50x50m2). Taking sampling using rowing boats and fishing gear with hooks 3. This research every day for 1 week.Sample observed in the laboratory of Fisheries Biology in Fisheries and Marine Faculty Universitas Riau. The observations made were meristic, morphometric and distribution index calculations. Research data were analyzed descriptively. The results showed there were differences in the distribution patterns of shrimp at each station. Stations 1 and 2 of shrimp distribution are uniform, while at station 3 distribution of shrimps is random. The measurement results of sample was found with total shrimp length (PTO) ranges from 110-250 mm, with an average of 176 mm and total body weight (BTO) ranging from 31-140 g with an average of 83.5 g. Shrimp caught during the study female were adult and juvenil, and which indicated that the mangrove ecosystem was a place of spawning for giant prawns.Keywords: Giant prawns Distribution, Mangrove Ecosystem, Water Quality, Rawa Mekar Jaya